PENGARUH PENGUASAAN PENYUSUNAN DAN PENGURAIAN VEKTOR TERHADAP HASIL BELAJAR PADA MATERI HUKUM NEWTON - Jafri Haryadi (Universitas Islam Sumatera Utara, 2022)
This study aims to determine the mastery of vector arrangement and decomposition on students' abilities in the matter of Newton's laws. In collecting data for this research, tests were given on the material of vector arrangement and decomposition and the material of Newton's laws. This test is to see the ability in mastery of the learning materials above. Data analysis shows that there is an influence of mastery of vector arrangement and decomposition on students' abilities in Newton's laws of matter. The results of the calculation of the correlation coefficient obtained an r value of 0.86 and continued with the significance test of the correlation coefficient, the t value was 9.70 which was greater than the t table value, which was 1.694. In the calculation of the coefficient of termination obtained a value of 0.7427. This result shows 74.27% which shows that there is a contribution of mastery of vector arrangement and decomposition to students' abilities in Newton's laws of matter.